India, "we Tamils", and Sri Lanka - Piyasena, S. (Senadhira), 1922-; Senadheera, R. Y. (Ruwan Yudagana), 1949- (Delhi, India : Sri Satguru Publications, 1987)
On Sri Lankan ethnic problem.
Keywords: Tamil (Indic people) -- Sri Lanka -- Politics and government; Sri Lanka -- Politics and government; Sri Lanka -- Ethnic relations; Tamil Nadu (India) -- Politics and government